Monitoring and Analysis of Spatiotemporal Variations in Poyang Lake (2016–2024) Using Sentinel-1/2 Imagery - Sun, Yuhao; Jin, Hailiang (International Journal of Natural Resources and Environmental Studies, 2025)
Timely and accurate information on dynamic open surface water is essential for under-standing long-term hydrological patterns and sustainable development. Frequent cloud cover limits the use of optical imagery for dynamic surface water observation, making it difficult to achieve high-frequency monitoring. A high-frequency surface water observa-tion dataset for Poyang Lake from 2016 to 2024 was constructed by employing a rapid ex-traction algorithm that integrates Sentinel-1/2 imagery. Subsequently, the spatiotemporal changes of the lake’s surface water over the 2016–2024 period. Our findings indicate that the extraction algorithm achieved a high degree of accuracy, with Overall Accuracies (OA) exceeding 95% and Kappa coefficients greater than 0.90. The dataset reveals a significant seasonal trend, with the maximum inundation area occurring in 2020 (5,179 km²) and the minimum in 2022 (3,196.04 km²). The water area typically peaks in June–July and recedes to its minimum in November–December. Permanent and temporary water bodies are de-creasing, while seasonal ones are increasing. The conversion between water body types was dominated by the reclassification of temporary and permanent water as seasonal water. These research findings provide key data on the recent hydrological dynamics of Poyang Lake.